2022
DOI: 10.1039/d2ce00585a
|View full text |Cite
|
Sign up to set email alerts
|

Crystal facet and phase engineering for advanced water splitting

Abstract: Water splitting is a promising approach to producing renewable hydrogen energy with zero carbon dioxide emission, and it has been intensively studied to improve conversion efficiencies over the past decades....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 267 publications
1
36
0
Order By: Relevance
“…Direct growth on the substrate usually generates low series resistance compared to that generated using a binder for binding to the surface of the electrode. (2) The boosting of the HER catalytic activity of the P-Co MOF/Co 3 S 4 sheet can be attributed to the binding energy of the Co ions: the higher binding energy of the Co 2+ ions and sulfur, which is partially negatively charged, results in increased attraction of hydride and protons for hydrogen evolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Direct growth on the substrate usually generates low series resistance compared to that generated using a binder for binding to the surface of the electrode. (2) The boosting of the HER catalytic activity of the P-Co MOF/Co 3 S 4 sheet can be attributed to the binding energy of the Co ions: the higher binding energy of the Co 2+ ions and sulfur, which is partially negatively charged, results in increased attraction of hydride and protons for hydrogen evolution.…”
Section: Discussionmentioning
confidence: 99%
“…However, hydrogen is not freely present in the atmosphere and must be obtained from the splitting of hydrogen-containing compounds such as water. 2,3 Hydrogen can be produced from water in three ways: photolysis, thermolysis, and electrolysis. [4][5][6] During water splitting, hydrogen is generated at the cathode, and oxygen is generated at the anode.…”
Section: Introductionmentioning
confidence: 99%
“…To boost the photocatalytic activity in material design, separating reduction and oxidation sites is an efficient method. Since the electronic structures and surface reactivity are different depending on crystal facets, facet-engineering can be used for separating oxidation and reduction sites [ 28 ]. Band alignment between different facets provides a route for charge carriers to separate.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is necessary to augment and expose them as much as possible to achieve vigorous photoelectrolysis. 71,72 Lots of studies have revealed that exceptionally active edges and defects can be induced by strain engineering, 73 plasma treatment, 74 foreign elements doping, 75 and so on. Li et al theoretically predicted and verified that elaborately strained and electrochemically generated sulfur vacancies in the basal plane of monolayer MoS 2 serve as highly active sites for hydrogen evolution reaction.…”
Section: Active Catalystsmentioning
confidence: 99%